Bentofauna rzeki Pichna Szadkowicka na odcinku od źródła w Zimnej Wodzie do ujścia z terenu uroczyska Wojsławice - Szczerkowska-Majchrzak, Eliza; Woziwoda, Beata (Biuletyn Szadkowski, 2014)
The aim of the study was the documentation of benthofauna from the Pichna Szadkowicka river flowing through the Wojsławice forest complex in the municipality of Szadek. The study was conducted in July 2013 at eight study sites. Among the collected material, many groups of invertebrates were distinguished, Gammaridae were dominant in the benthic community, Chironomidae, (Diptera) and representatives of the Mollusca (Sphaeridae) were subdominants. Invertebrates were most abundant among macrophytes (Glyceria.fiuitans) on the sandy bottom with a small fraction of fine particles of organic matter; there was no presence of animals in the stream headwaters area.